The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2174/1874091x00701010012
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts and Caveolae in Signaling by Growth Factor Receptors

Abstract: Lipid rafts and caveolae are microdomains of the plasma membrane enriched in sphingolipids and cholesterol, and hence are less fluid than the remainder of the membrane. Caveolae have an invaginated structure, while lipid rafts are flat regions of the membrane. The two types of microdomains have different protein compositions (growth factor receptors and their downstream molecules) suggesting that lipid rafts and caveolae have a role in the regulation of signaling by these receptors. The purpose of this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 217 publications
1
32
0
2
Order By: Relevance
“…From various previous reports, there is complexity and versatility on the role of caveolin-1 in the EGF-induced signaling pathway. They showed that caveolin-1 play an activatory or inhibitory role (5,12,28). This suggests that other factors are involved in EGF-induced signaling or some of which are cell-type specific.…”
Section: Discussionmentioning
confidence: 99%
“…From various previous reports, there is complexity and versatility on the role of caveolin-1 in the EGF-induced signaling pathway. They showed that caveolin-1 play an activatory or inhibitory role (5,12,28). This suggests that other factors are involved in EGF-induced signaling or some of which are cell-type specific.…”
Section: Discussionmentioning
confidence: 99%
“…Various growth factor receptors and cell signaling molecules have been found to be compartmentalized in the caveolae, suggesting an important role for caveolae in signal transduction [17]. Caveolin-1 (cav-1) is the principal structural protein of caveolae [18] that are abundantly present in terminally differentiated cells [19], including endothelial cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some domains are characterized by the presence of specific structural and regulatory proteins called caveolins, which, when present in appropriate amounts and with specific post-translational modification, can form caveolae [2,3]. The caveolin family consists of two ubiquitously expressed genes, caveolin-1 (Cav-1) and -2 (Cav-2), and one specifically expressed in smooth and skeletal muscles, caveolin-3 (Cav-3) [4,5].…”
Section: Introductionmentioning
confidence: 99%